(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Science fiction is a literary genre characterized by imaginative narratives, futuristic technologies, and innovative vocabulary. These distinctive features create specific challenges for translators, particularly when dealing with newly coined terms and speculative scientific concepts. The aim of this article is to examine the translation strategies commonly used in science fiction texts and to analyze how translators preserve both meaning and stylistic effect. The study emphasizes that the translation of science fiction requires not only linguistic competence but also creativity and cultural awareness. Effective translation strategies such as borrowing, calque, and descriptive translation allow translators to recreate the fictional world of the source text while maintaining readability for the target audience.